A STUDY ON RELATIONSHIP BETWEEN INNOVATIVE LEADERSHIP OF SCHOOL ADMINISTRATORS AND TEACHERS’ INNOVATIVE THINKING SKILLS UNDER PHITSANULOK PRIMARY EDUCATIONAL SERVICE AREA OFFICE 2 - Likitratjaroen, Benjawan; Wechayaluck, Nirada (Journal of MCU Nakhondhat, 2025)
This research aimed to 1) Study the innovative leadership of educational administrators 2) Study the innovative thinking skills of teachers 3) Study the relationship between the innovative leadership of educational administrators and the innovative thinking skills of teachers under the Office of the Primary Educational Service Area 2, Phitsanulok. This is a descriptive research, with the sample size determined from the Krejci and Morgan table, compared in proportion by district, and the data providers were 97 School administrators and 97 Teachers, totaling 197 People, using a simple random sampling method, using a questionnaire as the research tool, and analyzing the data using statistics, mean, standard deviation, and Pearson's product moment correlation coefficient. The research results found that 1) The innovative leadership of educational administrators was overall at a high level ( = 4.40). The aspect with the highest mean was creating an innovative organizational climate ( = 4.49), and the aspect with the lowest mean was risk management ( = 4.33). 2) Overall, the innovative thinking skills of teachers were at a high level ( = 4.40). The aspect with the highest mean was the aspect with the lowest mean was the aspect of connection skills ( = 4.46) and the aspect with the lowest mean was the aspect of observation skills ( = 4.32). 3) The relationship between the innovative leadership of school administrators and the innovative thinking skills of teachers, overall, had a positive relationship at a fairly high level (r = .685) with a statistical significance level of .05. Innovative leadership had a fairly high relationship with the innovative thinking skills in connection skills (r = .772) and innovative leadership had a fairly low relationship with the innovative thinking skills in observation skills (r = .375).